Utilization of Basil Leaf Extract as Anti-Mosquito Repellent: A Case Study of Total Mosquito Mortality (Aedes aegypti 3rd Instar). (February 2020) - Husna, Ismalia; Setyaningrum, Endah; Handayani, Tundjung Tripeni; Kurnia, Yogi; Palupi, Endah Kinarya; Umam, Rofiqul; Andriana, Bibin Bintang
Abstract: This study aims to determine the most effective concentration of extract that kills the larvae in the third instar Aedes aegypti, knowing the value of LC50 and LC90 anthen knowing the value of LT50 and LT90 of forest basil leaf extract (Ocimum sanctum). Research is using a completely randomized design with factorial, and the first factor is forest basil leaf extract with 5 level concentrations, there are 0.3%, 0.6%, 0.9%, 1.2%, 1.5%, and 0% as control, whereas the second factor is observation period that began after the death of the larvae. Observations were made up to 4320 minutes. The results showed the influence of forest basil leaf extract against third instar larvae mortality of Aedes aegypti, and the most effective concentration of basil leaf extract to kill the larvae was 1.5%. LC50 values of this study was 0.97%, and for the LC90 value was 1.42%. Value of LT50 and LT90 of this study is 5, 71 hours or 342, 31 and 17, 02 hours or 1021.22 minutes. The conclusion of this study is basil leaf extract forest affect mortality third instar larvae of Aedes aegypti, and the most effective concentration of extract was 1.5%.